Biomimetic Non-Heme Iron-Catalyzed Epoxidation of Challenging Terminal Alkenes Using Aqueous H2O2 as an Environmentally Friendly Oxidant - Fingerhut, Anja; Vargas-Caporali, Jorge; Antonio Leyva-Ramirez, Marco; Juaristi, Eusebio; Tsogoeva, Svetlana (Molecules, 2019)
Catalysis mediated by iron complexes is emerging as an eco-friendly and inexpensive option in comparison to traditional metal catalysis. The epoxidation of alkenes constitutes an attractive application of iron(III) catalysis, in which terminal olefins are challenging substrates. Herein, we describe our study on the design of biomimetic non-heme ligands for the in situ generation of iron(III) complexes and their evaluation as potential catalysts in epoxidation of terminal olefins. Since it is well-known that active sites of oxidases might involve imidazole fragment of histidine, various simple imidazole derivatives (seven compounds) were initially evaluated in order to find the best reaction conditions and to develop, subsequently, more elaborated amino acid-derived peptide-like chiral ligands (10 derivatives) for enantioselective epoxidations.
CRIS-Team WoS Importer:2019-10-18